Combined Analysis of DNA Methylome and Transcriptome Reveal Novel Candidate Genes Related to Porcine Escherichia coli F4ab/ac-Induced Diarrhea - Wenwen Wang; Chuanli Zhou; Hui Tang; Ying Yu; Qin Zhang; Qin Zhang (Frontiers in Cellular and Infection Microbiology, 2020)
Enterotoxigenic Escherichia coli (ETEC) that express F4 (K88) fimbriae are the principal microorganisms responsible for bacterial diarrhea in neonatal and pre-weaning piglets. To better understand the molecular effects of ETEC F4ab/ac infection, we performed a genome-wide comparison of the changes in DNA methylation and gene expression in ETEC F4ab/ac infected porcine intestinal epithelial cells. We characterized the pattern of changes in methylation and found 3297 and 1593 differentially methylated regions in cells infected with F4ab and F4ac, respectively. Moreover, 606 and 780 differentially expressed genes (DEGs) in ETEC F4ab and F4ac infected cells were detected and these genes were highly enriched in immune/defense response related pathways. Integrative analysis identified 27 and 10 genes showing inverse correlations between promoter methylation and expression with ETEC F4ab/ac infection. Altered DNA methylation and expression of various genes suggested their roles and potential functional interactions upon ETEC F4ab/ac infection. Further functional analyses revealed that three DEGs (S100A9, SGO1, and ESPL1) in F4ab infected cells and three DEGs (MAP3K21, PAK6, and MPZL1) in F4ac infected cells are likely involved in the host cells response to ETEC infection. Our data provides further insight into the epigenetic and transcriptomic alterations of ETEC F4ab/ac infected porcine intestinal epithelial cells, and may advance the identification of biomarkers and drug targets for predicting susceptibility to and controlling ETEC F4ab/ac induced diarrhea.